PENGARUH CAPITAL STRUCTURE DAN COMPANY GROWTH TERHADAP NILAI PERUSAHAAN DENGAN GOOD CORPORATE COVERNANCE SEBAGAI VARIABEL MODERASI - Neneng Maya Fadilah; Susi Dwi Mulyani (STMIK Widuri Jakarta, 2024)
This research was conducted to analyze the effect of capital structure and company growth on firm value with good corporate governance as a moderating variable. This study is focused on manufacturing companies in the consumer goods sector on the Indonesia Stock Exchange (IDX). Capital Structure and Company Growth are considered as key factors that can affect company value. GCG is also identified as an important element in improving company performance. Quantitative method with hypothesis testing approach is used in this research. The research sample consisted of 83 consumer non-cyclicals sector companies listed on the IDX in the 2021-2022 period. Data obtained from financial reports published by the IDX. Data analysis was performed using descriptive statistics and panel data regression using the fixed effect model (FEM) method. The results of the study show that capital structure and company growth have a significant positive effect on firm value. That is, the better the capital structure and company growth, the higher the company value. However, the implementation of GCG did not strengthen the effect of capital structure and company growth on company value.